(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT This research aims to find out the truth about what is called consensus in the modern era, after clarifying the concept of consensus and what is related to it, and to find out the opinions of scholars about the possibility of this through their sayings, and its inclusion under agreement or silent consensus. Research method: inductive-deductive. The most important search results are: 1.Consensus is considered one of the legislative sources and comes in third place after the Qur’an and Sunnah, and this confirms its role and importance. 2.Consensus has rank and strength in the prohibition of violating it, which confirms the role and importance of human beings in understanding and formulating appropriate legislation. 3.Consensus confirms the superiority of collective opinion over individual opinion, and this confirms the theory that consensus among contemporaries is nothing but the agreement of the majority. The resulting contemporary consensuses fall under the name of silent agreement and consensus.